Atopic keratinocytes induce increased neurite outgrowth in a coculture model of porcine dorsal root ganglia neurons and human skin cells - Roggenkamp, Dennis; Petersen, Marlen; Schmelz, Martin (The journal of investigative dermatology, 2012)
Skin of patients suffering from atopic eczema displays a higher epidermal nerve fiber density, associated with neurogenic inflammation and pruritus. Using an in vitro coculture system, allowing a spatially compartmented culture of somata from porcine dorsal root ganglion neurons and human primary skin cells, we investigated the influence of dermal fibroblasts and keratinocytes on neurite outgrowth. In comparison with dermal fibroblasts, keratinocytes induced more branched and less calcitonin gene-related peptide (CGRP)-immunoreactive nerve fibers. By adding neutralizing antibodies, we showed that nerve growth factor (NGF) and glial cell-line-derived neurotrophic factor (GDNF) are pivotal neurotrophic factors of skin cell-induced neurite outgrowth. Keratinocytes and dermal fibroblasts secreted different ratios of neurotrophic factors, influencing morphology and CGRP immunoreactivity of neurites. To investigate changes of the peripheral nervous system in the pathogenesis of atopic eczema in vitro, we analyzed neurite outgrowth mediated by atopic skin cells. Atopic keratinocytes produced elevated levels of NGF and mediated an increased outgrowth of CGRP-positive sensory fibers. Our results demonstrate the impact of dermal fibroblasts and keratinocytes on skin innervation and emphasize the role of keratinocytes as key players of hyperinnervation in atopic eczema.
Gesehen am 17.08.2018